Evaluation of Environmental Management System Implementation ISO 14001 at Imam Lastori Daruba's Port Morotai Island Regency - M. Reza Kusman; Elfira Resti Mulya; Hartati Kapita (International Journal of Education, Information Technology, and Others, 2020)
Imam Lastori Daruba Port is one of the piers that serves local loading and unloading routes located in Morotai Island Regency which is a type of regional port. The purpose of this writing is to know the evaluation of the implementation of iso 14001 environmental management system in imam lastori port of morotai island district, the research method used is data collection by way of interview and field observation by way of descriptive analysis. Thus the implementation of environmental management system must be in accordance with Law No. 32 of 2009 on Environmental Protection and Management.